The New Encyclopedia of Southern Culture : Volume 13: Gender - Abadie, Ann J.; Thomas, James G., Jr; Wilson, Charles Reagan; Ownby, Ted; Bercaw, Nancy (Book collections on Project MUSE., 2009)
The volume features 113 articles, 65 of which are entirely new for this edition. Thematic articles address subjects such as sexuality, respectability, and paternalism and investigate the role of gender in broader subjects, including the civil rights movement, country music, and sports. Topical entries highlight individuals such as Oprah Winfrey, the Grimke sisters, and Dale Earnhardt, as well as historical events such as the capture of Jefferson Davis in a woman's dress, the Supreme Court's decision in Loving v. Virginia, and the Memphis sanitation workers' strike, with its slogan, "I AM A MAN." Bringing together scholarship on gender and the body, sexuality, labor, race, and politics, this volume offers new ways to view big questions in southern history and culture.